Synthesis and anticancer activity of new quinazoline derivatives - Hatem A. Abuelizz; Mohamed Marzouk; Hazem Ghabbour; Rashad Al-Salahi (Elsevier, 2017)
In this study, a new series of quinazoline derivatives (3-26) was synthesized and characterized via physicochemical and spectral means. Treatment of 2-amino-5-methylbenzoic acid with butyl isothiocyanate resulted in the new 2-thioxoquinazolin-4-one (3). Alkylation and hydrazinolysis of the inherent thioxo group in (1-3) afforded the corresponding thioethers (4-23) and hydrazine derivatives (24 and 25), then 24 was further transformed into tricyclic derivative 26 via cyclocondensation reaction. Compounds 1 and 2, which were previously synthesized, were found to exhibit anticancer activity. The cytotoxicity of all compounds was evaluated in vitro against the HeLa and MDA-MB231 cancer cell lines, including 1 and 2 for comparison, using MTT assay. The treatment of the cells was performed with the synthesized compounds and gefitinib at 0, 1, 5, 10, 25, and 50 μM and incubated for 24 h in 50% DMSO. The IC50 values of the target compounds were reported in μM, using gefitinib as a standard. Our results indicated that all compounds exhibited significant in vitro cytotoxicity against both cell lines. While compounds 1-3 showed good activity, compounds 21-23 were found to be more potent than gefitinib. Thus, compounds 21-23 may be potential anticancer agents, with IC50 values ranging from 1.85 to 2.81 μM in relation to gefitinib (IC50 = 4.3 and 28.3 μM against HeLa and MDA-MB231 cells, respectively).